Pengendalian Kutu Beras (Sitophilus oryzae l.) Secara Organik - Rahma Rahma; Muhammad Indar Pramudi; Elly Liestiany (www.ulm.ac.id, 2024)
Rice weevils can cause damage to rice in warehouses, so it is necessary to control them in an environmentally friendly manner. The aim of this research was to determine the effect of various types of organic pesticides used on rice weevils (Sitophilus oryzae L.). This study used a completely randomized design (CRD), consisting of 6 treatments applied during the imago stage. Each treatment consisted of 4 replications so that the experimental units obtained were 24 experiments. The results of the research show that the use of vegetable pesticides has the potential to kill rice weevils. Mortality observations obtained very significantly different results, where the open eco enzyme (TT) treatment with a percentage of 72.50% was a treatment that had an influence on rice weevil mortality. All treatments were able to kill rice weevils. from percentage 35 to 72.5. All botanical pesticides used can suppress the rice weevil population for up to 4 weeks after application and there is an increase thereafter and repeated applications are necessary to suppress the population.